The Effect of Push-up Training on Tennis Volley Ability - Andre Igoresky; Yogi Andria; Arisman Arisman (Universitas PGRI Palembang, 2023)
The purpose of this study was to determine the effect of push-up training on the ability to hit volley tennis. This research technique used a quasi-experimental method, meaning that before being given this design treatment a pretest was carried out first. The research design used was one group pretest-posttest design. The sampling technique is purposive sampling. The number of research samples was 20 people. Strength data is done by push-ups. Volleyball ability test using the Dyer Tennis Test which aims to measure volleyball ability. From the results of processing and evaluation of recording using the normality test, testing the hypothesis using the t test, that push-up exercises affect the ability to hit the volley. This can be seen from the results of statistical evaluation through the calculation of the t-test formula with the criteria tcount 7.65 > than t table 1.73, with a confidence level of 0.95 or 95% (α=0.05) and the number of samples (N = 20). This shows that there is a significant effect due to the push-up treatment on the volley.